Beginning GIMP: From Novice to Professional, Second Edition - Peck, Akkana (Apress, 2012)
The first few chapters assume no knowledge at all of GIMP or of any other image-editing program. Later chapters will assume you’ve picked up these basics, and will build on them. Chapter 1 introduces GIMP’s various windows, menus, and interface conventions. GIMP has a somewhat different user interface from most other programs, so it helps to get an idea of how its windows and dialog boxes work together and how the menus are structured. Beginning with Chapter 2, you’ll dive into practical image-editing tasks. Chapters 2 through 6 each cover a different category of image operations—layers, drawing, selection, touching up—and each one describes a series of different and related techniques. Chapter 7 takes you on a whirlwind tour of the special effects available in GIMP. Then you’ll dive into more advanced topics in Chapters 8 through 10, which cover subjects such as color theory, layer mode effects, shading, perspective, image stacking, and panoramas. Chapter 11 explores scripts and plug-ins: how they work, how to install existing ones, and how to take one and tweak it to do something slightly different. I hope that even people with no programming experience will at least take a look at the scripting sections—there’s a lot you can do with GIMP scripts, even if you’ve never written a line of code before